2019
DOI: 10.21608/jhiph.2019.64463
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chemical Composition of Spirulina Platensis and its Effect on Fasting Blood Glucose and Lipid Profile in Diabetic Rats

Abstract: Background & Objective(s): Spirulina platensis is an incredibly powerful source of proteins, fibers and antioxidants. The aim of the study was to assess the nutritional value of Spirulina platensis cultivated in Egypt and study its effect on fasting blood glucose and lipid profile in diabetic rats. Methods: A total of one kilogram of Spirulina platensis was used in the study. The nutritional value of Spirulina platensis was characterized by measuring its proximate, vitamins, amino acids, minerals and antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
5
2
Order By: Relevance
“…It was reported that 175 μg/100 g of vitamin B 12 and 9.86 mg/100 g of vitamin E were detected in SP [ 19 ]. Other studies reported 162 μg/100 g of vitamin B 12 [ 23 ] and 60 mg/100 g vitamin E in SP [ 18 ] However, these results were inconsistent with the results of this study as the content of vitamin B12 was higher than reported in the previous studies and vitamin E was undetectable as shown in Supplementary Table S3 .…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…It was reported that 175 μg/100 g of vitamin B 12 and 9.86 mg/100 g of vitamin E were detected in SP [ 19 ]. Other studies reported 162 μg/100 g of vitamin B 12 [ 23 ] and 60 mg/100 g vitamin E in SP [ 18 ] However, these results were inconsistent with the results of this study as the content of vitamin B12 was higher than reported in the previous studies and vitamin E was undetectable as shown in Supplementary Table S3 .…”
Section: Resultscontrasting
confidence: 99%
“…Glutamic acid is the main non-essential amino acid (14.1%) followed by aspartic acid (8.52%) while leucine is the main essential amino acid represent (6.4%) followed by valine (5.3%) as presented in Figure 2 . Previously, the total protein content was reported to be 56.79% [ 18 ] and other studies reported it to be 62.84% [ 19 ], which was slightly below the results of this study. Other studies reported leucine as the main essential amino acid with a percentage of 5.5% and glutamic acid as the main non-essential amino acid with a percentage of 9.2% [ 17 ], which was in accordance with the results of this study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The filtrates were evaporated under nitrogen and the residues were re-dissolved in 1ml water for water soluble vitamins and in1 ml butanol for fat soluble vitamins that were quantified by HPLC. (Manz and Vuilleumier, 1988)and El-Moataaz et al (2019) analysis was carried out using an Agilent 1260 series. Phenolic compound determined with HPLC according to by (Abd El-Baky et al, (2009) analysis was carried out using an Agilent 1260 series.…”
Section: Determination Of Vitaminsmentioning
confidence: 99%
“…Spirulina not only has potential as a sustainable biofuel, but also as an animal feed ( 10 ). Nutrients of spirulina enrichening with protein, carbohydrates, balanced amino acids, carotenoids, fatty acids including γ-linolenic acid, vitamins, and minerals ( 11 , 12 ). Approximately half of the total spirulina production is currently used for livestock and fish feed.…”
Section: Introductionmentioning
confidence: 99%